The Effect of Leadership on the Performance of Torosiaje Jaya Village Performances, Popayato District, Pohuwato Regency - Widyawati Saleh; William I.S.Mooduto; Maman Musa (Journal of Economic, Business, and Administration (JEBA), 2021)
The performance of the village government, which is most important in the performance of its apparatus, has a very important role in determining a predetermined performance planning program. If the performance is good, the impact will be good, but if the performance is wrong, it will have a bad impact. This study aims to determine the influence of leadership on the performance of the village apparatus Torosiaje Jaya. This type of research is descriptive research with a quantitative approach. The type of data used is primary data and secondary data with data sourced from observations, questionnaires and documentation. The population in this study amounted to 32 people, where the village apparatus amounted to 16 village BPD 9 people and village health cadres 7 people. The results of this study were hypothesis testing in order to test the influence of leadership on the performance of village officials. It has been tested that the high and low performance of village officials can be influenced by leadership. The influence of leadership on the performance of village officials is 21.5%. The results of this study indicate that in general it confirms the hypothesis that has been stated previously that there is a significant influence of leadership on the performance of village officials.